Corneal biomechanical predictors of intraocular pressure elevation after intravitreal anti-VEGF injection - Sayaka Sumi; Ryo Asaoka; Shuichiro Aoki; Kohdai Kitamoto; Ryo Terao; Mariko Kawata; Tatsuya Inoue; Ryo Obata; Keiko Azuma (PLoS ONE, 2025)
Purpose To investigate whether corneal biomechanical parameters measured via Corvis ST can predict acute intraocular pressure (IOP) elevation following intravitreal anti-VEGF injection. Design Retrospective observational study. Subjects Forty eyes from patients with neovascular age-related macular degeneration or retinal vein occlusion who underwent anti-VEGF therapy. Methods IOP was measured using the Corvis ST immediately before and 10 minutes after injection. The following biomechanical parameters were evaluated: DA Ratio MAX (2mm), biomechanically corrected IOP (bIOP), Peak Distance, Deflection Amplitude Max, Integrated Radius, and Stress-Strain Index (SSI). Main outcome measures Acute post-injection IOP elevation (continuous) and IOP spikes ≥10 mmHg (binary). Results The mean IOP increased significantly from 14.5 ± 3.17 to 24.7 ± 7.44 mmHg post-injection (p < 0.0001). IOP spikes ≥10 mmHg occurred in 55% of eyes. On multivariate analysis, higher bIOP (β = +1.17, p = 0.048) and lower DA Ratio MAX (β = –5.40, p = 0.038) were independent predictors of IOP elevation. DA Ratio MAX was the only significant predictor of IOP spikes (OR = 0.70, 95% CI: 0.51–0.96, p = 0.035). ROC analysis showed that DA Ratio MAX alone (AUC = 0.739) outperformed bIOP (AUC = 0.607), with the combined model yielding the highest AUC (0.773). A cutoff of DA Ratio MAX ≤4.936 provided 81.8% sensitivity and 42.9% specificity for predicting spikes. Conclusions DA Ratio MAX (2mm), reflecting global ocular compliance, was a significant predictor of acute IOP spikes after anti-VEGF injection. Alongside bIOP, it may be useful for pre-injection risk stratification of pressure-related complications.